Capital is Dead. Long Live Capital! A Political Marxist Analysis of Digital Capitalism and Infrastructure - Maïa Pal; Neal Harris (tripleC: Communication, Capitalism & Critique)
There is a growing literature suggesting that the digital economy is taking us out of capitalism. While this manifests most notably as a diagnosis of ‘digital feudalism’ or ‘techno-feudalism’, a differing voice is McKenzie Wark, who suggests we have entered an entirely new mode of production altogether: ‘vectoralism’. This paper historicises and theorises our current conjuncture in relation to the potential multiplicity of modes of production, and the materiality and imperialism of telecommunication infrastructures. We approve of Wark's development of new concepts, rather than turning to ahistorical regurgitations like ‘neo-feudalism’. However, we argue that the mode of production lens is not adequate to trace what we consider as more granular changes and that it risks packaging old wine in new bottles. For example, Wark's vectoral claims remain grounded in infrastructures such as undersea cables that are used by corporations and states as strategies of legal and economic imperialism reminiscent of the 19th century world order. Instead of examining this topic through a mode of production lens, we contend that these phenomena are better traced through a processual (rather than functional) and socially determined (rather than economically determined) method of historical materialism. In this regard, we adopt an approach closer to that of E. P. Thompson and Political Marxists, such as Brenner and Wood. To support our argument, we turn to both wider Marxist theory on the mode of production, which we then anchor in empirical works from contemporary critical infrastructure and communication studies.